Machine strength grading of Argentinean Eucalyptus grandis : Main grading parameters and analysis of strength profiles according to European standards - Piter, Juan Carlos Jesús (2004)
The present paper reports the results of an investigation regarding the possibility of machine strength grading sawn timber of Argentinean Eucalyptus grandis. In order to assess the usefulness of each parameter for predicting the mechanical properties of this timber species, and to propose strength, stiffness and density profiles, an empirical research project with four samples of beams and one sample of boards subjected to bending, and another sample of boards subjected to tension parallel to the grain, was carried out. The results obtained with specimens in structural sizes reveal the more important single and combined parameters for machine strength grading this timber species, and allow to analyse strength, stiffness and density profiles in comparison with the international strength class system established in the European standard EN 338.